OTDR Strain and Force Sensing by POF on Geotextiles in a Geotechnical Application Test - Dengler, Simon Andreas; Luber, Michael; Neff, Léon; Hangen, Hartmut; Schmauß, Bernhard; Ziemann, Olaf; Engelbrecht, Rainer (Proceedings - 28th International Conference on Optical Fiber Sensors, OFS 2023, 2023)
With polymer optical fibers (POF) attached to geotextiles, optical time domain reflectometry (OTDR) can be used to measure strain of the geotextile spatially resolved in soil. We test the technique in a geotechnical application test and thus demonstrate the functionality of the sensor for field use.
CRIS-Team Scopus Importer:2024-12-16